Evaluation of the wound healing activity of twelve herbal and non-herbal remedies used in Sana’a-Yemen for the treatment of wounds and burns - Alasbahi, Rawiya H.; Groot, Maria J. (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Wound healing is a complex process of integrated and overlapping phases resulting in the restoration of structural and functional integrity of injured tissues. Wounds and burn wounds represent a significant burden on the patients and health care professionals worldwide. There is still an obvious lack of suitable wound healing drugs since most of the available products can have some side effects and limitations. Traditional medicine has been practiced by the indigenous people of Yemen from antiquity until today. However, many of herbal and non-herbal products, used for wounds treatment, have not been the subject of any scientific investigation. Hence, the aim of this study was to document and scientifically evaluate the claimed wound healing efficiency of twelve herbal and non-herbal remedies (nine plants, one mineral (potassium alum), one marine product (cuttlefish bone) and one animal product (honey) used in Sana’a by indigenous people to treat wounds and burns. Searching electronic databases has indicated various experimental studies demonstrating four distinct pharmacological activities (anti-inflammatory, antioxidant, antimicrobial activities and promoting various phases of wound healing) displayed by the raw materials, extracts, chemical groups and some isolated compounds of the studied herbal and non-herbal remedies. Moreover, it has been found that the studied remedies do not produce serious side effects and can be considered generally safe upon appropriate topical usage. This study provides scientific data that support the wound healing efficiency of the studied remedies and thus lend some scientific justification for their traditional use in Sana’a for the treatment of wounds and burns. These herbal and non-herbal remedies can be considered as leads for future materials for wound healing and therefore further experimental and clinical studies are required to validate their effectiveness and safety.